Weak effects of birds, bats, and ants on their arthropod prey on pioneering tropical forest gap vegetation. Issue 6 (19th April 2022) - Szefer, Piotr; Molem, Kenneth; Sau, Austin; Novotny, Vojtech
Abstract: The relative roles of plants competing for resources versus top‐down control of vegetation by herbivores, in turn impacted by predators, during early stages of tropical forest succession remain poorly understood. Here we examine the impact of insectivorous birds, bats, and ants exclusion on arthropods communities on replicated 5 × 5 m of pioneering early successional vegetation plots in lowland tropical forest gaps in Papua New Guinea. In plots from which focal taxa of predators were excluded we observed increased biomass of herbivorous and predatory arthropods, and increased density, and decreased diversity of herbivorous insects. However, changes in the biomass of plants, herbivores, and arthropod predators were positively correlated or uncorrelated between these three trophic levels and also between individual arthropod orders. Arthropod abundance and biomass correlated strongly with the plant biomass irrespective of the arthropods' trophic position, a signal of bottom‐up control. Patterns in herbivore specialization confirm lack of a strong top‐down control and were largely unaffected by the exclusion of insectivorous birds, bats, and ants. No changes of plant–herbivore interaction networks were detected except for decrease in modularity of the exclosure plots. Our results suggest weak top‐down control of herbivores, limited compensation between arthropod and vertebrate predators, and limited intra‐guild predation by birds, bats, and ants. Possible explanations are strong bottom‐up control, a low activity of the higher order predators, especially birds, possibly also bats, in gaps, and continuous influx of herbivores from surrounding mature forest matrix.